Internet connectivity disruption in Turkey (Turkey) - Voidly (2026)
CRITICAL severity disruption detected in Turkey. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: TR-2026-0053
Keywords: internet disruption; TR; disruption; critical